Remotely Productive: The Efficacy of Remote Work for Executives - Duchin, Ran; Sosyura, Denis (Review of Financial Studies, 2026)
We study the efficacy of remote arrangements between CEOs and firms. Such arrangements attract executive talent and overcome labor market segmentation but introduce frictions. Remote arrangements are associated with lower operating performance, firm valuation, and insider reviews. Using the private costs from uprooting the CEO’s spouse as an instrument for the CEO’s decision to seek remote work, we find similar negative effects. The performance decline increases for CEOs who live further away and who cross multiple time zones. The mechanisms include the CEO’s loss of information, short-termism, and consumption of leisure, such as recreational boats and beach homes.